Comparing the long-term prognosis of myocardial infarction with non-obstructive coronary arteries to myocardial infarction with obstructive coronary artery disease. (3rd October 2022) - Monteiro, E; Barbosa, J; Guimaraes, J; Fernandes, D; Costa, G; Gomes, R; Rosa, J; Campos, G; Baptista, R; Monteiro, P; Monteiro, S; Goncalves, F; et al.
Abstract: Background: The long-term survival rates of myocardial infarction with non-obstructive coronary arteries (MINOCA) patients is lower than in the general population. Nevertheless, there are conflicting results regarding the prognosis of MINOCA patients in comparison to myocardial infarction with obstructive coronary artery disease (MI-CAD) patients. Purpose: The aim of this study was to assess the long-term all-cause mortality of MINOCA patients and compare it to MI-CAD patients. Methods: Retrospective analysis of 2443 consecutively admitted patients for acute myocardial infarction (AMI), in a single coronary intensive care unit. Only patients with 5 years of follow-up and those who died before the 5-year mark were considered. Patients were divided into two groups according to the presence or absence of obstructive coronary artery disease on angiography (≥50% stenosis). Demographic characteristics, symptoms at presentation, past medical history, laboratory characteristics and medication at discharge were compared using the Mann-Whitney U or χ 2 test (according to variable type) to ensure comparability between groups. Five-year all-cause mortality was the target endpoint. Five-year survival was modelled through the Cox proportional hazard regression model. The variable of interest (MINOCA vs MI-CAD) and possible confounders that displayed statistically significant differences in the initial demographic analysis were included in univariable Cox regressions, and those with statistically significant associations were included in a multivariable model. Those that displayed non-significant associations in the multivariable model were subsequently removed until we were left with significant associations only, giving us an adjusted hazard ratio. Results: Comparison between groups is presented in table 1. MINOCA patients were younger and more often women. They were less likely to have smoking habits, diabetes, or a previous history of AMI. They had a lower Killip class, as well as lower troponin I, serum creatinine and low-density lipoprotein cholesterol at admission. On the other hand, they had higher left ventricular ejection fractions. They were also less likely to have beta-blockers or aspirin prescribed at discharge. All-cause mortality at 5 years was 13.1% among MINOCA patients and 28.3% among MI-CAD patients, with an unadjusted hazard ratio (HR) of 0.421 (95% CI 0.322–0.550), p<0.001. Adjusting for known confounders, the HR was 0.461 (95% CI 0.261–0.816), p=0.008. Conclusions: Compared with MI-CAD patients, those with MINOCA were slightly younger and had fewer comorbidities. In spite of having a worse long-term prognosis when compared to the general population, MINOCA patients have a significantly higher 5-year survival rate than MI-CAD patients, even after adjustment of confounding factors. Funding Acknowledgement: Type of funding sources: None.